Evaluation of simple hematological screen for early diagnosis of neonatal sepsis - Waliullah, SM; Islam, MN; Siddika, M; Hossain, MA; Jahan, I; Chowdhury, AK (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):41-47. The abstract of this article is available on the PubMed website